The Mongol Empire : Genghis Khan, His Heirs and the Founding of Modern China - Man, John, 1941- (London Corgi Books, 2015)
''The Mongol Empire forever changed the course of history. Driven by an inspiring vision for peaceful world rule, Genghis Khan - mass-murdering barbarian to his enemies, genius and demi-god to his people - united warring clans and forghed an empire that spanned Asia, bringing people, cultures and religiosn together and opening intercontinental trade. Later his grandson, Kublai Khan, fuelled by the belief that heaven had given the world to the Mongols, doubled the empire's size until, in the late thirteenth century, he and his family controlled one sixth of the world's land area. Along the way, he conquered China, made Beijing his capital and gave the nation the borders it has today, establishing the roots of the twenty-first century superpower."
Include Color Illustration, Map, Bibliography and Index
Keywords: Mongols -- Kublai Khan, 1216-1294 -- Genghis Khan, 1162-1227